Evaluation of the Effect of Axial Length on Foveal Microstructure: A Comparative Optical Coherence Tomography Angiography Study - Kahramanoglu, Fatih; Alyamaç Sukgen, Emine; Albayrak, Muzaffer Talha (Scientific Reports in Medicine, 2025)
Objective: Myopia, characterized by an increase in the eye’s axial length, is a common refractive error that can lead to degenerative changes in the retina and optic nerve. The purpose of this study was to evaluate the effects of different axial length (AL) values on retinal and optic nerve head structures using Optical Coherence Tomography (OCT) and Optical Coherence Tomography Angiography (OCT-A).Method: This prospective cross-sectional study, included 150 patients (150 eyes) with cataracts, aged between 18 and 69 were. Patients were divided into five groups based on their AL values. Following ophthalmological examination, retinal nerve fibre layer (RNFL) and ganglion cell complex (GCC+IPL) thicknesses were measured with OCT, while foveal and peripapillary vascular density were measured with OCT-A. The obtained data were statistically compared among the AL groups.Results: The study revealed a significant thinning of RNFL and GCC+IPL thicknesses as AL increased (p
Keywords: Optical coherence tomography angiography; Myopia; Axial length